Could Mozambique become a hydrogen hub? - Hanlon, Joseph (Mozambique News Reports & Clippings, 2021)
The proposal for the Mphanda Nkuwa dam 60 km downstream from Cahora Bassa, and using the same water to generate more electricity, is back on the table. The dam has been proposed since the colonial era, but there has never been a market for the electricity. Producing hydrogen would be the perfect market. In this special issue, we look at Mphanda Kkuwa and the potential for hydrogen.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; GP - Tete; L - english / inglês; infrastructure - energy / infrastrutura - energia; natural resources / recursos naturais

Vale moves to exit coal business - Argus Media (2021)
In its first step to exit the coal business, Brazilian mining firm Vale will acquire all stakes held by Japanese trading house Mitsui in the Moatize coal mine and Nacala corridor coal infrastructure in Mozambique.
Keywords: #Reporting & Media / Reportagem & Mídia; *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; extractive industries / indústrias extractivas; natural resources / recursos naturais

Mozambique: Syrah Resources resumes graphite mining ahead of schedule after year's stoppage (Mozambique, 2021)
Australian mining company Syrah Resources has resumed production of graphite ahead of schedule at its Balama mine in Cabo Delgado, northern Mozambique, it said in a statement to shareholders on Tuesday. The plant's activities were halted in late March last year following the country's implementat
Keywords: #Reporting & Media / Reportagem & Mídia; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; natural resources - mining / recursos naturais - mineração; natural resources / recursos naturais; private sector / setor privado

Altona Rare Earths soars as it enters MoU to acquire rare earths project (Vox Markets, 2021)
Shares in Altona Rare Earths soared by over 60% today following the news that the group has entered into an MoU to acquire up to 70% in the Monte Muambe Rare Earths Project. Should it choose to proceed with the investment following a 90-day due diligence period, the project would represent its first venture into a carbonatite hosted REE asset.
Keywords: #Reporting & Media / Reportagem & Mídia; G - Mozambique / Moçambique; G - central / centro; GP - Tete; L - english / inglês; natural resources - mining / recursos naturais - mineração; natural resources / recursos naturais

Moma Titanium Minerals Mine, Mozambique - Mining Technology | Mining News and Views Updated Daily - Mining Technology (Mining-technology, 2021)
Moma, one of the world’s biggest titanium mineral deposits, is located 160km from the city of Nampula in Mozambique, Africa. It is owned and operated by Kenmare Resources. The mine contains the titanium minerals ilmenite, rutile and zircon, which are used as feedstock to produce titanium dioxide pigment. It started production of heavy mineral concentrate (HMC) containing these three minerals in April 2007. It produced 1,201,100t of HMC and shipped approximately 853,100t of finished products in 2020. Kenmare carried out an expansion at the mine ten years ago to fulfil the growing demand for titanium dioxide feedstock in the market. The expansion was aimed to increase the design capacity of the mine by 50% while increasing the mine’s reserve estimate and annual production of HMC. Construction work on the expansion began in December 2010 and the works were completed in December 2013. The expanded mine has a mine life of more than 100 years. The first shipment of concentrated mineral sands was dispatched from Mama in Q2 2019, following the commissioning of the product stream in Q4 2018. The Moma mine had more than 1,420 employees at the end of 2019.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Nampula; L - english / inglês; extractive industries / indústrias extractivas; natural resources - mining / recursos naturais - mineração; natural resources / recursos naturais